A Humanistic and Naturalistic Approach to the Dialogue Between Heavenly Monotheistic Religions = Humanistični in naturalistični pristop k dialogu med monoteističnimi religijami - Halil, Hüseyin (Edinost in dialog, 2022)
The earlier encounter of three monotheistic religions (Christianity, Judaism and Islam) dates back to the first quarter of the 7th century AC when the Qurʾ ān was revealed to Muḥammad, the prophet of Islam, so that he could warn the polytheistic tribes and the people of the book who had allegedly corrupted Abraham’s belief system. In the understanding of this new religion that is based on the same religious and cultural roots as the previous two religions (Christianity, Judaism), Qurʾānic theological perspective and narrative are final revisions made by God and revealed to the prophet Muḥammad. So, the first meetings between them began under the shadow of these sorts of challenges. These encounters caused a contention as to which side has more coherent, reasonable and divine understanding of God, rather than providing agreeable, inclusive and egalitarian dialogue. Therefore, in this article, we will firstly examine the role played by the Qur'ānic verses and major exegetes who have represented the interpretative tradition in Islamic culture for centuries. Secondly, with the concept of the human-centrism, we will bring a new approach to the God-centred dialogue which was almost restricted to the theological competition, to sort out the challenges caused by this contention.